- Analisis Yuridis Terhadap Saksi Korban Dibawah Umur Yang Disumpah Dalam Kasus Tindak Pidana Pencabulan (Studi Kasus Putusan Nomor 1162/Pid.B/2021/PN.Bdg) - Nada Samyra; Setiyono (Reformasi Hukum Trisakti, 2023)
According to the requirements of the Criminal Procedure Code (KUHAP), a kid under the age of 15 is not allowed to provide testimony as a witness who has been sworn in, making it impossible for the judge to review, consider, and decide on a criminal case using this testimony as legitimate evidence. The judge's considerations that classify a minor as a victim-witness who offers testimony under oath are against the Criminal Procedure Code, and thus phrasing of the issue is whether the statement from a minor can be characterized as valid evidence. Research methodology: a style of standardizing legal inquiry employing optional information as necessary and supplementary evidence. This information is provided subjectively and comes to light at the conclusion. The outcomes of the research show that there are violations of law that result in minors being declared incapable of being legal evidence. Discussion: because of that the legal considerations given by the panel of judges were inappropriate because judges did not need to swear underage children in giving testimony at trial. The conclusion of this study is that giving an oath to a minor and not the only witness involved in the case is an act that violates the Criminal Procedure Code.